α Effect and Magnetic Diffusivity β in Helical Plasma Under Turbulence Growth - Kiwan Park (Universe)
We investigate the transport coefficients <semantics>α</semantics> and <semantics>β</semantics> in plasma systems with varying Reynolds numbers while maintaining a unit magnetic Prandtl number (<semantics>PrM</semantics>). The <semantics>α</semantics> and <semantics>β</semantics> tensors parameterize the turbulent electromotive force (EMF) in terms of the large-scale magnetic field <semantics><mover>B¯</mover></semantics> and current density as follows: <semantics>⟨u×b⟩=α<mover>B¯</mover>−β∇×<mover>B¯</mover></semantics>. In astrophysical plasmas, high fluid Reynolds numbers (<semantics>Re</semantics>) and magnetic Reynolds numbers (<semantics>ReM</semantics>) drive turbulence, where <semantics>Re</semantics> governs flow dynamics and <semantics>ReM</semantics> controls magnetic field evolution. The coefficients <semantics>αsemi</semantics> and <semantics>βsemi</semantics> are obtained from large-scale magnetic field data as estimates of the <semantics>α</semantics> and <semantics>β</semantics> tensors, while <semantics>βtheo</semantics> is derived from turbulent kinetic energy data. The reconstructed large-scale field <semantics><mover>B¯</mover></semantics> agrees with simulations, confirming consistency among <semantics>α</semantics>, <semantics>β</semantics>, and <semantics><mover>B¯</mover></semantics> in weakly nonlinear regimes. This highlights the need to incorporate magnetic effects under strong nonlinearity. To clarify <semantics>α</semantics> and <semantics>β</semantics>, we introduce a field structure model, identifying <semantics>α</semantics> as the electrodynamic induction effect and <semantics>β</semantics> as the fluid-like diffusion effect. The agreement between our method and direct simulations suggests that plasma turbulence and magnetic interactions can be analyzed using fundamental physical quantities. Moreover, <semantics>αsemi</semantics> and <semantics>βsemi</semantics>, which successfully reproduce the numerically obtained magnetic field, provide a benchmark for future theoretical studies.